Answer:
B
Step-by-step explanation:
just multiply and add
Answer:
2916 square inches
Step-by-step explanation:
Surface area of rectangular prism:
Here, area of the top of the prism is not included.
l = 24 in ; b = 20 in ; h = 16 in
Surface area = lb + 2bh + 2lh
= 24 * 20 + 2*20*16 + 2*24 *16
= 480 + 640 + 768
= 1888 sqaure inches
Surface area of triangular prism:
length = 24 in ; a = b = 16 in ; base = 20 in and height = 13 in
![\sf \text{Base area=$2*\dfrac{1}{2}*base *height = base *height$}](https://tex.z-dn.net/?f=%5Csf%20%5Ctext%7BBase%20area%3D%242%2A%5Cdfrac%7B1%7D%7B2%7D%2Abase%20%2Aheight%20%3D%20base%20%2Aheight%24%7D)
= 20 * 13
= 260 square inches
Surface area = length*(a +b) + base area
= 24*(16+16) + 260
= 24 * 32 + 260
= 768 + 260
= 1028 square inches
Surface area of composite figure = 1888 + 1028
= 2916 square inches
A= -2
aa= -2(-2)= 4
Hence, the correct answer is the second option, 4.
Answer:
The ordered pair solution is (-2,2)
Step-by-step explanation:
Here, we want to get the ordered pair solution to the system of linear equations
From the first equation, we can have it that;
-2x = 16-6y
Now, we can substitute this into the second equation as follows;
From; -4x -3y = 2
2(-2x) - 3y = 2
2(16-6y) - 3y = 2
32 - 12y - 3y = 2
32-15y = 2
-15y = 2-32
-15y = -30
y = -30/-15
y = 2
Recall;
-2x + 6y = 16
substitute for the value of y
-2x + 6(2) = 16
-2x + 12 = 16
-2x = 16-12
-2x = 4
x = 4/-2
x = -2
Answer:
Answer is in the explanation
Step-by-step explanation:
I don't know exactly word from word what your choices look like...
but I can describe per each box what happened in my own words:
First box: They multiply first equation by 3 and the second equation by 2 to obtain the equations in that first box.
Second box: They subtracted the two equations in the first box to obtain 1x+0y=2 which means 1x=2 or x=2 (this is called solving a system by elimination
Third box: They used their first original equation (before the multiplication manipulation) and plug in the value they got for x which was 2 giving them 3(2)-2y=10
Fourth box: They simplified the equation 3(2)-2y=10 by performing the multiplication 3(2) giving them 6-2y=10
Fifth box: They subtracted 6 on both sides giving them -2y=4
Sixth box: They divided both sides by -2 giving them y=-2
I will summarize then what I wrote above:
1st box: Multiplication Property of Equality
2nd box: Elimination
3rd box: Substitution (plug in)
4th box: Simplifying
5th box: Subtraction Property of Equality
6th box: Division Property of Equality